Melão in natura como dieta exclusiva para bovinos: um estudo de caso - Melo, Vitor Lucas de Lima (Universidade Federal Rural do Semi-Árido, 2020)
Due to the well-known importance of brazilian cattle, associated with technological evolution and a greater awareness of social and environmental responsibility and the sustainability of production, more and more alternatives are being sought to replace the traditional sources of energy and protein in cattle feed, because those are the most expensive ingredients in ruminant diets, encouraging a research for alternative ingredients to replace such traditional ingredients. The objective was to evaluate the effect of using fresh melon as an exclusive diet for beef cattle and its effects on ruminal physiology, blood biochemical parameters and liver histology, of 18 bovine animals, male and female, of the Nelore and Holstein breed with an average age of 25 months, from the municipality of Baraúnas / RN, where the animals were fed during the termination period exclusively with fresh melon. The slaughter was carried out under municipal inspection, where samples of rumen liquid were collected. The ruminal fluid examination was performed immediately after collection and will consist of macroscopic analyzes of sedimentation and flotation time, in addition to pH measurement and the methylene blue reduction test. The ruminal pH had a mean minimum of 7.20 and a maximum of 7.33 considered normal according to the literature consulted, as well as color and odor. Sedimentation and fluctuation tests and bacterial reductive activity in all cases were longer than 8 minutes, which may indicate simple indigestion, blood metabolite values were within the normal range for the species with the exception of the glucose rate which showed values ranging from 130.33 to 171.50 mg / dL, well above the values considered normal. Hepatic histology showed mild tissue damage and accumulation of glycogen, these factors being probably due to a diet rich in soluble carbohydrates. The exclusive melon diet is an alternative to replace part of the diet of beef cattle, it is important to observe the adaptation of the animals to the diet and the time to which they will be subjected to it.
Keywords: Alimentação alternativa; Bovinocultira de corte; Cucumis melo L.; Alternative feed; Beef cattle,; Cucumis melo L.; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL